Desain Miniatur Plant Simulator Pompa Air Kotor Panel Kontrol Relai Kontaktor - Susilo; Nanang Setio Pambudhi; Agus Andrianto; Dimas Eriyanto; Milzam Brillian Santanaa (Politeknik Negeri Malang, 2025)
Wastewater management played a crucial role in maintaining environmental cleanliness and health, where water pumps held a vital position. However, manually operated pump systems were often inefficient and posed potential health risks if failures occurred. This research aimed to design and create a miniature plant simulator for wastewater pumps utilizing a relay contactor control panel. This miniature plant was specifically designed to automatically simulate the operation of a wastewater pump system, offering a solution to replace the often inefficient manual methods. The research process commenced with identifying the main components required, such as a three-phase induction motor, contactors, thermal overload relays, and associated sensors. Subsequently, the design and construction of both the simulator and its control panel were meticulously carried out. Implementation involved comprehensive testing of each component's functionality and the overall system's integrity, including individual component testing and evaluation under simulated system failure conditions like overload and no flow. The research results clearly demonstrated that the built miniature plant simulator functioned effectively as expected. The automatic control system employing relay contactors proved efficient and safe in operating the water pump, capable of managing various water levels and detecting abnormal conditions such as overload and no flow. This miniature plant could serve not only as a valuable learning tool but also as a promising prototype for the development of larger and more complex wastewater pump control systems in the future.